Application of the photoelectronic mixing device to optical measurement of presence, distance and velocity - Gulden, Peter; Vossiek, Martin; Heide, Patric; Schwarte, R. (30th European Microwave Conference, EuMC, 2000)
The novel photoelectronic mixing device (PMD) brings about new opportunities in the area of optical 3-D imaging and velocity measurement. This paper reviews the PMD principle and points out the similarities between PMD systems and conventional radar systems. An experimental setup for range measurement with the PMD is shown. For the first time radar modulation techniques have been applied to the PMD device. Experiments stress that they are well suited for 3-D imaging. Previously these modulation concepts were only employed with either radar or sophisticated optical systems. © 2000 IEEE.
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.LEH.applic